Republic of Croatia : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2019)
This Selected Issues paper explores how intersectoral vulnerabilities and risks have shifted over 2001-17, and especially after the Global Financial Crisis. It analyzes financial positions at the sectoral levels deposit taking institutions and non-financial corporations, households, the public sector, and the Croatian National Bank by disaggregating them into instruments, currencies, and maturities. The paper has employed balance sheet analysis (BSA) to gauge cross-sectional exposures and risks. The BSA approach is a method to study an economy as a system of interlinked sectoral balance sheets. The policies to reduce the remaining vulnerabilities have also been discussed in the paper. Standard macroeconomic indicators demonstrate that Croatia's overall external vulnerabilities have declined since 2010. However, the balance sheet matrix shows little improvement in reduction of important cross-sectoral dependencies and liabilities to the rest of the world over 2010-17. One of the recommendations made is to encourage deleveraging through specific policy options and strategies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet